2017
DOI: 10.1186/s12931-017-0600-3
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone inhibits myofibroblast differentiation and lung fibrosis development during insufficient mitophagy

Abstract: BackgroundPirfenidone (PFD) is an anti-fibrotic agent used to treat idiopathic pulmonary fibrosis (IPF), but its precise mechanism of action remains elusive. Accumulation of profibrotic myofibroblasts is a crucial process for fibrotic remodeling in IPF. Recent findings show participation of autophagy/mitophagy, part of the lysosomal degradation machinery, in IPF pathogenesis. Mitophagy has been implicated in myofibroblast differentiation through regulating mitochondrial reactive oxygen species (ROS)-mediated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 29 publications
2
63
0
Order By: Relevance
“…The present study validates prior impressions that pirfenidone has pleiotropic actions on both the immune system and ECM (table 1) [16][17][18]. The study also reports, for the first time, that pirfenidone may influence metabolism of hyaluronan, a major component of the ECM that regulates tissue injury and repair [19].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The present study validates prior impressions that pirfenidone has pleiotropic actions on both the immune system and ECM (table 1) [16][17][18]. The study also reports, for the first time, that pirfenidone may influence metabolism of hyaluronan, a major component of the ECM that regulates tissue injury and repair [19].…”
supporting
confidence: 90%
“…In vivo (BLM model) KURITA [17] Restoration of insufficient mitophagy/enhancement of PARK2 expression In vitro (fibroblasts) DIDIASOVA [18] Inhibition of GLI transcription factors In vitro (fibroblasts) TGF: transforming growth factor; FGF: fibroblast growth factor; IL: interleukin; BLM: bleomycin; CEMIP: cell migration-inducing and hyaluronan-binding protein; GLI: glioma-associated oncogene homologue.…”
Section: Song [16]mentioning
confidence: 99%
“…Although PRKN-mediated direct regulation of inflammation cannot be completely excluded, we speculate that SASP attributed to accelerated cellular senescence is responsible for the inflammatory phenotype in CS-exposed prkn KO mice PRKN overexpression was sufficient for inducing mitophagy and inhibiting cellular senescence in response to CSE exposure ( Figure 5), indicating that PRKN induction is a potentially promising geroprotective modality of treatment for COPD with reduced PRKN and accelerated cellular senescence. We have recently reported that anti-fibrotic PFD is a candidate agent for inducing PRKN expression [23]. Although a significant increase in PRKN expression levels was detected at 10 μg/ml PDF in HBEC, which is comparable to the levels of maximum plasma concentration of PFD in a clinical setting, 5-fold higher concentration (50 μg/ml) was needed to demonstrate sufficient mitophagy with an anti-senescence property ( Figures S6 and 7).…”
Section: Discussionmentioning
confidence: 80%
“…We have recently reported that pirfenidone (PFD), an antifibrotic modality of treatment for idiopathic pulmonary fibrosis, induces autophagy/mitophagy through the enhancement of PRKN expression in lung fibroblasts (LF) [23]. Hence, the role of PFD-mediated autophagy/mitophagy in the regulation of CSE-induced cellular senescence was examined in HBEC.…”
Section: Pirfenidone Attenuates Cse-induced Cellular Senescence Via Imentioning
confidence: 99%
“…It is generally recognized that alveolar epithelial cell injury and inflammation lead to aberrant proliferation of fibroblasts, resulting in an exaggerated deposition of extracellular matrix (ECM) in the lung parenchyma and eventually leading to lung function damage (2). However, the molecular mechanism underlying IPF is not fully understood, and there is still lack of effective treatment for IPF aside from lung transplantation, even though a number of studies have reported the anti-fibrotic effects of nintedanib and pirfenidone on lung fibrosis (3)(4)(5). Therefore, it is of great value to reveal the pathogenesis of IPF and to explore more effective therapeutic strategies and drugs for the treatment of IPF.…”
mentioning
confidence: 99%